anonymous
  • anonymous
Solve the following system of equations. 2a – 3b + c = 10 2a – 2b – 2c = 2 a + 3b + 2c = –1
Mathematics
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

ghazi
  • ghazi
use determinant to solve above equation
anonymous
  • anonymous
idk wat that means
amistre64
  • amistre64
there are different methods that all come to the same results; since you have not defined a method, the determinant is suitable

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
the determinant is kidna useless you can tell if it's not factorable once you have the equation narrowed to 2 variables.
anonymous
  • anonymous
just use substitution :D!
amistre64
  • amistre64
ugh, substitution on these takes forever!!
amistre64
  • amistre64
id eliminate :)
anonymous
  • anonymous
how do u eliminatte
amistre64
  • amistre64
you scale the eqauations so that you can combine them and eliminate one of more of the variables
amistre64
  • amistre64
R1, 2a – 3b + c = 10 R2, 2a – 2b – 2c = 2 R3, a + 3b + 2c = –1 R3(-2), R2(-1) R1, 2a – 3b + c = 10 R2, -2a + 2b + 2c =-2 R3, -2a -6b -4c = 2 R1+R2, and R1+R3 R1, 2a – 3b + c = 10 R2, 0 - b + 3c = 8 R3, 0 - 9b - 3c = 12 R2(-9) R1, 2a – 3b + c = 10 R2, 0 +9b -27c = -72 R3, 0 - 9b - 3c = 12 R2 + R3 R1, 2a – 3b + c = 10 R2, 0 +9b -27c = -72 R3, 0 + 0 - 30c =-60
amistre64
  • amistre64
-30c = -60 c = 2
amistre64
  • amistre64
R1, 2a – 3b + (2) = 10 R2, 0 +9b -27(2) = -72 R1, 2a – 3b = 10-2 R2, 0 +9b = -72+54 b = -18/9 = -2 R1, 2a – 3(-2) = 8 R1, 2a + 6 = 8 a = (8-6)/2 = 1
amistre64
  • amistre64
2a – 3b + c = 10 1 -2 2 ------------- 2 + 6 + 2 = 10 2a – 2b – 2c = 2 1 -2 2 -------------- 2 + 4 - 4 = 2 a + 3b + 2c = –1 1 -2 2 ------------------ 1 -6 + 4 = -1
anonymous
  • anonymous
wow that is a lot of work i do not like these so much do you?
amistre64
  • amistre64
i find them tedious
amistre64
  • amistre64
it takes longer to show the work than it does to actually get the answer :)
anonymous
  • anonymous
thankyou for ur help!
amistre64
  • amistre64
i hope it was helpful :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.